Assessing the conservation status of tree fern Cibotium arachnoideum (C. Chr.) Holttum - Titien Ngatinem Praptosuwiryo (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Praptosuwiryo TN. 2020. Assessing the conservation status of tree fern Cibotium arachnoideum (C.Chr.) Holttum. Biodiversitas 21: 1379-1384. Cibotium arachnoideum (C.Chr.) Holttum (Cibotiaceae), is a large terrestrial fern with an upright or prostrate rhizome having densely shining reddish-brown of rigid hairs and one or two pairs of sori with two indusia forming a small cup on each lamina-segment. This tree fern is a rare species and strictly distributed in the Malesian region. The study aims to assess the conservation status of C. arachnoideum by using the 2012 IUCN Red List Catagories and Criteria (version 3.1.). Population size was estimated and observed both based on specimens deposited at the Herbarium Bogoriense (BO) and field studies in Sumatra. The area of occupancy (AOO) of this species is 44 km2. Cibotium arachnoideum is occurred in severely fragmented locations in the West Malesian region, in 2 locations, viz. Sumatra and Borneo. Sumatra has only two subpopulations, and Borneo has nine subpopulations. The number of mature individuals was only found 372 in one location of North Sumatra and 19 individuals in one location of Bengkulu. Therefore, C. arachnoideum is proposed as an endangered species, En: B2ab (i,ii,iii) + C2a (ii).